Patrimoniality in non-heritage cities: case of Crixás, Goiás, Brasil - Lima, Luana Nunes Martins de (2020)
Crixás (Goiás, Brasil) se analiza en este artículo desde su génesis colonial hasta el contexto actual que indica el abandono en la defensa de su patrimonio cultural. Several economic, political and social events have led to the almost complete destruction of a set of movable and immovable cultural goods in the urban space. The objective of the research was to identify the extent to which absences and permanences in the urban landscape and / or in the collective memory build a sense of particular patrimoniality. It was possible to recognize that such a sense, originating from the heritage-memory-place relationship, tensions the material-symbolic dialectic of the local heritage, overlapping the institutional recognition or the official discourse of conservation of built goods. For the analysis, bibliographic and documentary researches, participant observation in local cultural manifestations, techniques of oral history and interviews (semi-structured, narratives and photo-interviews) were carried out.